ANALISIS KOMPARASI KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PT. BANK JAGO, Tbk - Ahsan Fathur Rahman; Eri Bukhari; Ery Teguh Prasetyo (Jurnal Ilmiah Akuntansi dan Manajemen, 2022)
Analysis of financial performance before and after the acquisition is a fundamental step in making investments. This study aims to determine the comparison of the financial performance of PT. Bank Jago Tbk, which is the result of the acquisition of PT. Bank Artos Indonesia. The ratios used include: Return on Assets (ROA), Capital Adequacy Ratio (CAR), Operating Expenses and Operating Income (BOPO), Non-Performing Loans (NPL) and Loan to Deposit Ratio (LDR) before and after acquisition activities at PT. Bank Jago Tbk. The method in this study uses quantitative methods in data collection and the sample used in this study is the 2017-2021 financial report. This research uses Paired Samples T Test in answering the hypothesis . The results in this study indicate that the variables of Capital Adequacy Ratio (CAR), Operating Expenses and Operating Income (BOPO), Non-Performing Loans (NPL) and Loan to Deposit Ratio (LDR) show significant differences before and after the acquisition while the Return on Assets variable (ROA) showed no significant difference.